Whole-Brain Monosynaptic Afferent Projections to the Cholecystokinin Neurons of the Suprachiasmatic Nucleus - Yuan, Xiang-Shan; Wei, Hao-Hua; Xu, Wei; Wang, Lu; Qu, Wei-Min; Li, Rui-Xi; Huang, Zhi-Li (Frontiers in Neuroscience, 2018)
The suprachiasmatic nucleus (SCN) is the principal pacemaker driving the circadian rhythms of physiological behaviors. The SCN consists of distinct neurons expressing neuropeptides, including arginine vasopressin (AVP), vasoactive intestinal polypeptide (VIP), gastrin-releasing peptide (GRP), cholecystokinin (CCK), and so on. AVP, VIP, and GRP neurons receive light stimulation from the retina to synchronize endogenous circadian clocks with the solar day, whereas CCK neurons are not directly innervated by retinal ganglion cells and may be involved in the non-photic regulation of the circadian clock. To better understand the function of CCK neurons in non-photic circadian rhythm, it is vital to clarify the direct afferent inputs to CCK neurons in the SCN. Here, we utilized a recently developed rabies virus- and Cre/loxP-based, cell type-specific, retrograde tracing system to map and quantitatively analyze the whole-brain monosynaptic inputs to SCN CCK neurons. We found that SCN CCK neurons received direct inputs from 29 brain nuclei. Among these nuclei, paraventricular nucleus of the hypothalamus (PVH), paraventricular nucleus of the thalamus (PVT), supraoptic nucleus (SON), ventromedial hypothalamic nucleus, and seven other nuclei sent numerous inputs to CCK neurons. Moderate inputs originated from the zona incerta, periventricular hypothalamic nucleus, and five other nuclei. A few inputs to CCK neurons originated from the orbital frontal cortex, prelimbic cortex, cingulate cortex, claustrum, and seven other nuclei. In addition, SCN CCK neurons were preferentially innervated by AVP neurons of the ipsilateral PVH and SON rather than their contralateral counterpart, whereas the contralateral PVT sent more projections to CCK neurons than to its ipsilateral counterpart. Taken together, these results expand our knowledge of the specific innervation to mouse SCN CCK neurons and provide an important indication for further investigations on the function of CCK neurons.